Preoperative high-intensity interval training is effective and safe in deconditioned patients with lung cancer: A randomized clinical trial - Chetna Bhatia; Bengt Kayser (Medical Journals Sweden, 2019)
Background: The outcome of surgery in deconditioned patients can be improved through prehabilitation. This study examined the effect of prehabilitation in patients diagnosed with lung cancer. Methods: Candidates for lung cancer resection were assigned to high-intensity interval training (n = 74) or usual care (n = 77). Cardiopulmonary exercise testing and 6-min walk test were performed before and after training. High-intensity interval training consisted of 2-3-weekly, 2 × 10-min series of cycling at peak power, measured with cardiopulmonary exercise testing prior to training, with a 15-s on-off duty cycle, preceded by a 5-min warm-up and followed by a 5-min cool-down. Work-rate, heart-rate, saturation, dyspnoea and leg effort were monitored. Results: Waiting time (median 25 days) allowed a median of 8 high-intensity interval training sessions to be performed. Adherence to mean high-intensity interval training was 87% (18% standard deviation; SD). High-intensity interval training power increased (23 watt, 95% confidence interval (95% CI): 20-26 watt), as did heart rate (14 bpm, 95% CI 11-16 bpm). Resting heart rate (-6 bpm, 95% CI -4 to -7 bpm) and heart rate 1 min post-cool-down decreased (-5 bpm, 95% CI -4 to -7 bpm). Aerobic capacity increased after high-intensity interval training (14%, 95% CI 3-26%), as did peak power output (median 7%, 95% CI 2-13%), but not after usual care. Six-min walk test score increased after high-intensity interval training (median 20%, 95% CI 14-26%), but not after usual care. Conclusion: Short-term high-intensity interval training is feasible in deconditioned patients and increases cardio-respiratory fitness and walking capacity.